(untitled) (Medicine Today, 2020)
Introduction:Acute Pancreatitis is a medical emergency, which is one of the most common conditions for hospital admission. Very few studies have yet investigated in Bangladesh. Objective of this study was to define demographic characteristics, clinical profile & underlying etiologies. Materials and Methods: This hospital based cross sectional descriptive study was performed in Sir Salimullah Medical College Mitford Hospital, Dhaka & North East Medical College, Sylhet, Bangladesh from January 2015 to December 2017. One hundred and five consecutive patients of acute pancreatitis (AP) were enrolled for this study. Clinical features and investigations were systematically recorded. Diagnosis of acute pancreatitis was made by the presence of the two of the three following criteria: i. abdominal pain consistent with the disease ii. serum amylase and /or lipase greater than three times from the upper limit of normal, and/or iii. characteristic findings of abdominal imaging. Results: Total of 105 patients took part in the study, of them 65 were male. The mean age was 42.76 ±15.88. Abdominal pain & vomiting was the most common mode of presentation. Gall stone and hypertriglyceridaemia were responsible of 20% of acute pancreatitis. Ascariasis also causes acute pancreatitis in two patients. Conclusion: Acute pancreatitis is a condition associated with high morbidity and mortality. Ascariasis also causes acute pancreatitis in endemic area. Patients usually respond conservative treatment but endoscopic treatment is effective in few cases. Surgery is rarely required. Medicine Today 2020 Vol.32(1): 21-24